2001
DOI: 10.1002/sia.1085
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the oxidation resistance of high‐temperature turbine materials

Abstract: This overview highlights some of the key factors in understanding the protective ability of aluminum oxide scales for current gas turbine engine alloys and coatings. Dense, phase-pure, slow-growing and adherent scales are required. In most cases, solutions have been found through educated empiricism, with more complete understanding often lagging by decades. Nevertheless, the relentless application of new techniques to answer old questions has often provided radically different viewpoints and pointed the way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 39 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…(1) In both the Ni 3 Al and IC221M alloys under slow heating and cooling, the ZrO 2 formation occurs before the Al 2 O 3 formation is detected. (2) With rapid heating and cooling, as expected, the Ni 3 Al alloy did not show extensive oxidation and, in contrast, the IC221M alloy showed rapid oxidation. (3) In the IC221M alloy, an abrupt change in the lattice parameter of ␥Ј was observed, in conjunction with the initiation of ZrO 2 formation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…(1) In both the Ni 3 Al and IC221M alloys under slow heating and cooling, the ZrO 2 formation occurs before the Al 2 O 3 formation is detected. (2) With rapid heating and cooling, as expected, the Ni 3 Al alloy did not show extensive oxidation and, in contrast, the IC221M alloy showed rapid oxidation. (3) In the IC221M alloy, an abrupt change in the lattice parameter of ␥Ј was observed, in conjunction with the initiation of ZrO 2 formation.…”
Section: Discussionsupporting
confidence: 62%
“…[2] The present work is part of the ongoing efforts to extend this knowledge to high-volume-fraction ␥Ј alloys close to the Ni 3 Al composition. Previous work on Ni 3 Al alloys has indicated that the oxidation resistance of these alloys is generally good compared to other nickel-based alloys.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, attention has been focused on the failure of the E/TBC system on the front side of the samples far from the edges. Under these aspects, the results obtained in this study are rated by comparing with data reported for furnace cycling tests of TBCs on Ni-based superalloys [38], albeit the spallation lifetime substantially depends also on sample geometry, thermal gradients during heating and cooling periods and layer thickness. The thermal cycling behaviour of the latter TBC systems depended upon the bond coats, their pre-treatments and the substrates.…”
Section: Discussionmentioning
confidence: 85%
“…[5] Alternatively, scale adhesion may be improved by removing S, either by hydrogen (H 2 ) annealing or melt fluxing. A quantitative correlation between scale adhesion and S and a literature survey can be found in recent reviews, [6,7] with specific attention to low S superalloys. [8][9][10] Many of the above precepts may be applied to the cyclic oxidation behavior of TBCs and their delamination failure.…”
Section: Introductionmentioning
confidence: 99%